Determinants of Employee Performance at PT Perkebunan Nusantara 1 Regional 5 Ajong Gayasan - Salman Farizi; Nur Alifia Husna (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
Human resources were considered one of the most valuable assets in achieving organizational goals. Effective human resource management through talent management, human resource planning, and human resource auditing was expected to enhance employee performance. This study aimed to examine the effects of talent management, human resource planning, and human resource auditing on employee performance at PT. Perkebunan Nusantara I Regional 5 Ajong Gayasan. A quantitative research approach was employed, and data were collected by distributing questionnaires to all 70 warehouse employees using a saturated sampling technique. The data were analyzed using multiple linear regression analysis. The findings showed that talent management (X1) did not have a significant effect on employee performance (Y). In contrast, human resource planning (X2) and human resource auditing (X3) have positive and significant effects on employee performance (Y). Furthermore, talent management, human resource planning, and human resource auditing simultaneously have a significant effect on employee performance. These findings indicate that strengthening human resource planning and implementing effective human resource audits are essential for improving employee performance, while the implementation of talent management still requires further improvement to maximize its contribution to organizational performance. Keywords: Talent management, Human resource planning, Human resource auditing, Employee performance.